(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article describes the effects of yeast strains, enzyme preparations and mineral components used to optimize the composition of the nutrient medium used in the production of bioethanol by processing grape waste. Methods of obtaining second-generation biofuel are one of the current topics. Biofuel production from food waste helps to solve two problems at the same time. Firstly, it causes a reduction in the negative impact on the environment by eliminating food waste, and secondly, it is used as a renewable energy source, taking into account the increasing need for energy sources resulting from economic and demographic growth. is used. In the study, the optimization of the composition of the nutrient medium and the achievement of increasing the amount of bioethanol produced in the process of alcoholic fermentation are compared with the example of experiments.